A Study of MPPT Charge Controller Roles in Photovoltaic Energy Management - Ahmad Nordin, Afiqah; Sazali, Norazlianie (Emerging Advances in Integrated Technology, 2022)
Energy management system for controlling a microgrid. Management of power flow for minimizing the cost of electricity and reduction of loss of energy produced by renewable energy sources. This paper is about a study of MPPT charge controller roles in photovoltaic energy management. PV systems usually provide a photovoltaic array, the MPPT charge controller, storage battery, and dc load. The MPPT charge controller is important. It continuously tracks the maximum power point and delivers the maximum possible power to the battery at any given point in time. In this project, a dc-dc boost converter circuit has been simulated using the software of Proteus. The microcontroller in Arduino NANO is used and will read the voltage values, the current values, and process all the calculations. Perturb and observe (P & O) algorithm is used to transfer maximum power from the PV panel which is executed using a microcontroller. The Arduino NANO is programmed using the software of Arduino IDE. Liquid Crystal Display (LCD) is used to display the voltage, current, and power from the PV module and PWM from the MPPT charge controller. The benefit of this project is to achieve high efficiency and low cost of photovoltaic (PV) model for the design of PV systems with a simple MPPT.